Komunikasi Efektif SBAR dengan Kualitas Pelaksanaan Timbang Terima Diruangan Rawat Inap - Masya Indriani Simon; Agust A. Laya; Sri Wahyuni (PPNI UNIMMAN, 2025)
The implementation of weigh-in is a technique for handing over information related to the patient's condition in a short and adequate manner which if not done correctly, it greatly contributes to medical error. Therefore, nurses have to be able to increase effective communication with SBAR in the implementation of weigh-in to realize patient safety goals in hospitals. The purpose of this study was to find out the corelation between SBAR effective communication and the quality of weigh-in implementation and Receiving in the Inpatient Room of Maria Walanda Maramis Hospital North Minahasa. The research was conducted using a descriptive analytical method of Cross sectional. Samples were taken based on the number of respondents of 43 people using Purposive Sampling. Data collection was carried out by questionnaire and observation. Furthermore, the collected data was processed by a chi-square statistical test with a α≤ safety level of 0.05.The results of the study showed that there was an effective communication of SBAR with the quality of the implementation of weigh-in in the inpatient room of Maria Walanda Maramis Hospital in North Minahasa, ρ=0.000 p value less than α≤ value of 0.05.The conclusion in this study is that there is a correlaton between effective communication of SBAR and the quality of the implementation of weigh-in in the inpatient room of Maria Walanda Maramis Hospital in North Minahasa. It is hoped that nurses will further improve the implementation of effective SBAR communication in the implementation of arbitration.,